Design of Novel Mycobacterium tuberculosis Pantothenate Synthetase Inhibitors: Virtual Screening, Synthesis and In Vitro Biological Activities. Issue 2 (17th February 2015) - Devi, Parthiban Brindha; Jogula, Sridhar; Reddy, Asireddy Parameshwar; Saxena, Shalini; Sridevi, Jonnalagadda Padma; Sriram, Dharmarajan; Yogeeswari, Perumal
Abstract: Pantothenate synthetase (PS) enzyme involved in the pantothenate biosynthetic pathway is essential for the virulence and persistent growth of Mycobacterium tuberculosis (MTB). It is encoded by the panC gene, and has become an appropriate target for developing new therapeutics for tuberculosis. Here we report new inhibitors active against MTB PS developed using energy based pharmacophore modelling of the available proteininhibitor complex (3IVX) and virtual screening of a large commercial library. The e‐pharmacophore model consisted of a ring aromatic (R), negative ionizable (N) and acceptor (A) sites. Compounds5 and10 emerged as promising hits with IC 50 s 2.18 µM and 6.63 µM respectively. Further structural optimization was attempted to optimize lead 10 using medicinal chemistry approach and six compounds were found to exhibit better enzyme inhibition compared to parent compound lead 10 (<6 µM). Abstract :